Significant Acute Kidney Injury Due to Non-steroidal Anti-inflammatory Drugs: Inpatient Setting - Mehul Dixit; Thuy Doan; Rebecca Kirschner; Naznin Dixit (MDPI AG, 2010)
In the United States non-steroidal anti-inflammatory drugs (NSAID) are freely available over-the-counter. Because of the adverse effects on the kidneys and the popularity of these drugs, unregulated use of NSAIDs is an under recognized and potentially dangerous problem. Fifteen inpatients, mean age of 15.2 ± 2.3 years (five males, 10 females), were referred to nephrology for acute kidney injury. All patients admitted to taking ibuprofen and six also consumed naproxen. None of the patients had underlying renal diseases at the time of admission. Nine patients had proteinuria and 12 had hematuria (including one with gross hematuria). One patient had nephrotic syndrome but the condition resolved spontaneously without steroids and has remained in remission for four years. Two patients required dialysis. Only one of the dialyzed patients required steroid therapy for recovery of renal function. The mean duration of hospitalization was 7.4 ± 5.5 days. The serum creatinine peaked at 4.09 ± 4.24 (range 1.2-15.3) mg/dL. All patients recovered renal function with normalization of serum creatinine to 0.71 ± 0.15 mg/dL. The estimated GFR (glomerular filtration rate) at peak of renal failure was 38.2 ± 20.5 mL/min but did improve to a baseline of 134 ± 26.2 mL/min (range 89-177, p < 0.01). However, the duration from onset to normalization of serum creatinine was 37 ± 42 days indicating that majority of patients had abnormal renal function for a prolonged period. In conclusion, NSAIDs pose a significant risk of renal failure for significant duration and as an entity may be under recognized.